Clinical research priorities in emergency medicine. (9th October 2013) - Keijzers, Gerben; Thom, Ogilvie; Taylor, David; Knott, Jonathan
Abstract Objective To determine the clinical research priorities of Fellows of the Australasian College for Emergency Medicine (ACEM) in order to inform the strategic research agenda specific to multicentre clinical research. Methods An anonymous survey of all ACEM Fellows (FACEMs) listed on the ACEM researcher database was conducted between January and March 2013. Results Of 108 FACEMs invited to participate, 54 (50%) responded. Over half of respondents (61%) had a higher research degree but only a minority (24%) had funded research positions. The top research categories identified as priorities were resuscitation, trauma, cardiology, ED ultrasound, acute behavioural disturbance and geriatrics. The most common specific sub‐categories included anterior chest pain, fluid resuscitation in trauma, and drug therapy for both atrial fibrillation and acute behavioural disturbance. Several specific research questions related to chest pain, resuscitation/sepsis, stroke, paediatrics and pulmonary embolus. Conclusion The findings provide guidance and support for research areas amenable to collaborative multicentre clinical research within emergency medicine. Discussion rounds are planned to translate these perceived research priorities to actual priorities.